ANALISA PENGARUH IPM, PMTB, BELANJA TIDAK LANGSUNG DAN BELANJA LANGSUNG TERHADAP PDRB KABUPATEN DAN KOTA DI PROVINSI JAWA TENGAH TAHUN 2015-2019 - Agusta, Fauzy Adrian; Arianti, Fitrie (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This study aims to analyse the effect of HDI, GFCF, indirect expenditures and direct expenditures on GRDP in 35 regency and municipality in Central Java Province from 2015 to 2019. The dependent variable in this study is GRDP in 35 regencies and cities in Central Java Province. Four independent variables are the Human Development Index (IPM), Gross Fixed Capital Formation (GFCF), indirect spending, and direct spending. The method used in this study is panel data regression. Based on the study results, all independent variables, namely HDI, GFCF, indirect spending, and direct spending, positively and significantly impact GRDP in 35 regencies and cities in Central Java Province. Therefore, if a region improves the quality of its human capital, investment, and regional spending, it can be associated with an increase in GRDP.Keywords: HDI; GFCF; Indirect Expenditures, and Direct Expenditures; on GRDP